Whole-Blood MicroRNA Sequence Profiling and Identification of Specific miR-21 for Adolescents With Postural Tachycardia Syndrome - Lin, Jing; Shen, Jie; Liu, Juan; Cheng, Wenjie; Li, Lintian; Jiao, Fuyong (Frontiers in Neuroscience, 2022)
Objective To establish whether whole-blood MicroRNA (miRNA) profiles differ between postural tachycardia syndrome (POTS) sufferers and control subjects, and to identify the miRNA that regulates plasma H2S. Study design High-throughput sequencing was used to obtain whole-blood miRNA expression profiles for 20 POTS sufferers and 20 normal children. The thresholds for defining DEmiRNAs (differentially expressed miRNAs) were: an adjusted DESeq P of less than 0.05 and a log2-fold variation of greater than or equal to three. The DEmiRNA target genes were identified using RNAhybrid and miRanda, and only those identified by both were considered. The combined effects of the DEmiRNAs were determined using KEGG pathway analysis. Another 40 POTS and 20 normal patients were used as validation subjects. Plasma H2S was determined with a sulfide electrode, and flow-mediated vasodilation (FMD) was performed with a color Doppler ultrasound system. MiRNAs were analyzed using QRT-PCR. Results: Thirteen DEmiRNAs were identified through high-throughput sequencing. In the 60-member validation group, the thirteen miRNAs were verified again and it turned out that the miR-21was significantly elevated and could diagnose POTS with a 100% specificity and 92.5% sensitivity. 198 and 481 genes, respectively, were shown to be targeted by the 13 DEmiRNAs when P values of 0.01 and 0.05 were used. The target genes of hsa-miR-21-5p was SP1 when the P value is less than 0.01. DEmiRNAs were significantly enriched in 36 pathways (P <0.05), in which PI3K/Akt signaling was closely related to vascular function. In the validation subjects, the plasma H2S and FMD was higher in the POTS sufferers (P <0.05). Conclusion: Elevated whole-blood miR-21 levels serve as an indicator for POTS and may explain the increased plasma H2S observed in POTS sufferers.